Baby Massage is Useful in Stunting Prevention - Sukamti, Sri; Junengsih, Junengsih; Aticeh, Aticeh; Sriwenda, Djuju (Women, Midwives and Midwifery, 2024)
Background: Stunting, underweight, and extreme thinness continue to plague Indonesian children's growth; stunting, underweight, and extreme thinness are still common in children under the age of five. One possible countermeasure is providing tactile stimulation (touch) to malnourished babies. Baby massage is a type of tactile stimulation that can help a baby's sense of touch develop. Purpose: This study aims to determine the effect of baby massage on baby weight gain to prevent stunting in babies below the standard weight curve. Methods:  Quasi-experimental pre-posttest one-group design is used in this study. The study included 21 malnourished babies under two who weighed less than the normal weight curve. Purposive sampling was used to collect the samples. The study was conducted at an independent midwife clinic providing baby massage services. Data was collected using questionnaires and checklist sheets. The dependent t-test is used in data analysis to perform a correlation test. Results: The results show a significant relationship between baby massage and baby weight gain (P-value 0.001; average weight in the first week was 7714.29 grams, 7909.52 grams in the second week, 8095.24 grams in the fourth week, 8180.95 grams in the fifth week, and 8228.57 grams in the sixth week). The p-value is 0.001, indicating a significant difference between the average increase in body weight from the first to the sixth week. Conclusion: Weekly massages given consistently and repeatedly to malnourished babies can help them gain weight and prevent stunting. The recommended action is to improve the mother's ability to massage the baby independently to increase the baby's weight